Effect of Guar Gum on 3D Printing Properties of Purple Sweet Potato Gels - Lei CAI; Lei FENG; Yayuan XU; Meimei NIE; Dajing LI; Tiesong ZHENG; Dongxing YU (Shipin gongye ke-ji, 2023)
In order to develop nutrient rich personalized food, the effects of different guar gum concentrations on rheological, gelation, 3D printing, microstructural properties and functional groups of purple sweet potato gels were explored by rheological analysis, scanning electron microscopy and Fourier transform infrared spectroscopy. The results showed that apparent viscosity, storage modulus, loss modulus, L*, gumminess and chewiness of purple sweet potato gels increased, the micro pore size decreased, and the gel network structure was denser with the increase of guar gum concentration. The water holding capacity of purple sweet potato gels was 80.49% and the gel strength was 72.67 g when guar gum concentration was 1.6%. The addition of guar gum significantly improved 3D printability of purple sweet potato gels. When guar gum was added at 1.2% and 1.6%, 3D printed purple sweet potato gels had good formability, the average accuracy deviation was less than 1%, and the stability deviation was less than 5% after 6 hours of storage. The addition of guar gum would not produce new functional groups in 3D printed purple sweet potato gels, but mainly strengthened interactions of CH2 bonds and O-H bonds. This study provided a theoretical basis for the development of 3D printing of plant-based ingredients, which was very important for the personalization of functional foods.